Overcoming Steric Hindrance in Aryl‐Aryl Homocoupling via On‐Surface Copolymerization. Issue 18 (14th May 2019) - Urgel, José I.; Di Giovannantonio, Marco; Gandus, Guido; Chen, Qiang; Liu, Xunshan; Hayashi, Hironobu; Ruffieux, Pascal; Decurtins, Silvio; Narita, Akimitsu; Passerone, Daniele; Yamada, Hiroko; Liu, Shi‐Xia; et al.
Abstract: On‐surface synthesis is a unique tool for growing low‐dimensional carbon nanomaterials with precise structural control down to the atomic level. This novel approach relies on carefully designed precursor molecules, which are deposited on suitable substrates and activated to ultimately form the desired nanostructures. One of the most applied reactions to covalently interlink molecular precursors is dehalogenative aryl‐aryl coupling. Despite the versatility of this approach, many unsuccessful attempts are also known, most of them associated to the poor capability of the activated precursors to couple to each other. Such failure is often related to the steric hindrance between reactants, which may arise due to their coplanarity upon adsorption on a surface. Here, we propose a copolymerization approach to overcome the limitations that prevent intermolecular homocoupling. We apply the strategy of using suitable linkers as additional reactants to the formation of fully conjugated polycyclic nanowires incorporating non‐benzenoid rings. Abstract : On‐surface synthesis can lead to the formation of novel carbon‐based materials. Here, a copolymerization strategy circumventing the unsuccessful homocoupling of sterically hindered precursor molecules is presented.